Morphology of the adult male and pupal exuviae of Glyptotendipes (Glyptotendipes) glaucus (Meigen 1818) (Diptera, Chironomidae) using scanning electron microscope (SEM) - Kownacki, Andrzej; Woznicka, Olga; Szarek-Gwiazda, Ewa; Michailova, Paraskeva; Czaplicka, Anna (Zootaxa, 2017)
In this paper, a study of the morphology of the pupa and male imago of Glyptotendipes (G.) glaucus (Meigen 1818) was carried out, with the aid of a scanning electron microscope (SEM). The SEM provided additional valuable information on the morphology of the species. Adult male head, antenna, wing, leg, abdomen, hypopygium, pupal cephalothorax and abdomen were examined. It is emphasized that SEM was not often used in Chironomidae studies. The present results confirm SEM as a suitable approach in carrying out morphological and taxonomical descriptions of Chironomidae species.